GE_GERICHTE C/24750/2017 vom 6. Mai 2019 - GE Cour de justice (2019)
MAINLEVÉE DÉFINITIVE;PRESCRIPTION;TAXATION CONSÉCUTIVE À UNE PROCÉDURE | CPC.126.al1; CPC.321.al1; LP.80.al1; LIFD.165.al3; ALCP.369